PEMBATASAN PERKEMBANGAN PERMUKIMAN KAWASAN PINGGIRAN SEBAGAI UPAYA PENGENDALIAN PERKEMBANGAN KOTA SEMARANG - Bitta Pigawati; Nany Yuliastuti; Fadjar Hari Mardiansjah (TATALOKA, 2017)
The need to settle is a basic need of people that must be fulfilled. The weakness of law enforcement and public awareness on the spatial planning implicate the emergence of settlement areas in various locations that are less suitable for its allocation. The settlements in Semarang are growing very fast and tending to be unfocused. The increase of built area especially in residential areas indicates reduced of green open space and the catchment area. This phenomenon begins to appear in the outskirts of Semarang. This study aims to examine the development of settlements that occurred during the period of 10 years in the outskirts of the city of Semarang. It includes 10 districts, further, this study used descriptive quantitative and spatial analysis. The results showed that the completeness of the factor is the most influential factor on the development of settlements. Settlements tend to develop regularly with a regular pattern. The residential development areas also occur in the catchment area and in locations that are not suitable for allotment, so that limitation efforts should be made on the development of settlements. There are still some locations that are possible for the construction of settlements in the outskirts of Semarang. The government needs to follow up this issue by providing information to the community, so that the development of settlement is in accordance with the direction of urban development